Treatment adherence and short-term outcomes of smoking cessation outpatient clinic patients - Karadoğan, Dilek (Tob Induc Dis, 2018)
INTRODUCTION: Previous studies have shown that adherence to treatment is fundamental to success in smoking cessation. However, smoking cessation medication regimens are limited significantly by the struggle to adhere to them. This study was conducted to evaluate the factors associated with treatment adherence and quitting success in a group of patients that applied to our smoking cessation outpatient clinic (SCC). METHODS: Patients that applied to SCC between April 2015 and December 2016 who were evaluated, found suitable for smoking cessation interventions and started pharmacological treatment were included in this study. Only those who could be reached by phone three months after their first application became participants. Those who had used the prescribed treatment for at least 30 days were grouped as treatment-adherent. RESULTS: In total, data for 346 patients were evaluated. Mean (±SD) age was 44.3±13.9 years; most of them were male (63%), primary school graduated (36.1%), self-employed (43.7%), and had no comorbid diseases (71%). Bupropion was started in 52% of the patients, that rate was 35.8% for varenicline and 12.1% for a combination of the nicotine patch and gum. Mean days for treatment use was 20.9±18.5; 59% of the patients were non-adherent to their treatment and 51.7% had only one control visit number. Adverse reactions due to treatment were recorded in 25% of participants, and at their third month 37.9% of them had quit smoking. In multivariate logistic regression analysis, increase in control visit number, absence of adverse reaction, and varenicline use, were each associated with higher treatment adherence (p<0.001) and only being in the treatment-adherent group was associated with quit success (OR=3.01, 95% CI: 1.88–4.81, p=0.001). CONCLUSIONS: This study showed that most patients did not use their prescribed SC treatments adequately; a main factor that affects quit success is treatment adherence. There is a need for closer monitoring and follow-up to ensure adequate use of treatment of patients.